Pelatihan Dasar Kepemimpinan Siswa sebagai Sarana Pengembangan Bakat Kepemimpinan Siswa yang Jujur, Percaya Diri, Tanggungjawab, Disiplin, dan Kreatif - Hendri Hermawan Adinugraha; Mila Sartika; Sih Darmi Astuti; Mahmud Mahmud (Universitas Mathla'ul Anwar Banten, 2021)
BASIC STUDENT LEADERSHIP TRAINING AS A MEANS TO DEVELOP HONEST, CONFIDENCE, RESPONSIBILITY, DISCIPLINE, AND CREATIVE STUDENT LEADERSHIP TALENTS. The purpose of basic student leadership training as a means of developing honest, confident, responsible, disciplined, and creative student leadership talents is to provide additional skills on leadership, public speaking, personality, and entrepreneurship for students who are administrators of the Intra School Student Organization. (OSIS) SMP Muhammadiyah 4 Semarang. This dedication shows that there are 2% of students in the Intra School Student Organization (OSIS) SMP Muhammadiyah 4 Semarang who still do not have a complete understanding of leadership, but 91.3% of the students of the Intra School Student Organization (OSIS) SMP Muhammadiyah 4 Semarang able to explain about leadership. Their public speaking ability is at 65.2%. Their personality knowledge is 73.9% and 56.5% understanding and simulating entrepreneurship. The ability of the leadership of the Intra School Student Organization (OSIS) SMP Muhammadiyah 4 Semarang is higher than other material indicators. Because testing other materials uses practices such as public speaking and entrepreneurship simulations.